What will schools gain by leading on the new EYFS?. (2nd April 2020) - Cowley, Sue
Abstract : Those which are taking the opportunity to embed the revised EYFS learning and development requirements ahead of nurseries and pre-schools may gain some ground, but it will be hard work.